Studi Performansi Mesin Pelontar Pakan Ikan terhadap Gaya Sentrifugal - Perdana Putra Kelana; Rizqi Ilmal Yaqin; Rangga Bayu Kusuma Haris; Alfakhri Alfakhri; A Marsha Alviani (Balai Riset dan Standardisasi Industri Samarinda, 2021)
The fish feed thrower machine can disperse the feed over a wide coverage area in a short time. Throw distance is an important parameter that must be considered in a fish feed thrower machine. Distribution of feed from the fish feed thrower machine is due to the centrifugal force. This study aims to analyze the rotational speed (RPM) of the fish feed thrower machine 360° against throw distance and centrifugal force of the feed grains. Maximum results obtained for throw distance, throw speed and centrifugal force occur at RPM 600. Farthest throw distances from the feed codes 781-1, 781 and 782 are 2.20 m, 1.89 m and 1.66 m. Maximum throw speeds of the feed codes 781-1, 781 and 782 are 14,667 m/s, 12,583 m/s and 11,083 m/s. Maximum centrifugal force of the feed codes 781-1, 781 and 782 are 0.504x10-3 N, 2.711x10-3 N and 5.796x10-3 N. This shows that the centrifugal force on the feed grains causes the rotational speed (RPM) to affect the distance and speed of the feed.